2021
DOI: 10.1002/ajp.23335
|View full text |Cite
|
Sign up to set email alerts
|

Dramatic decline in a titi monkey population after the 2016–2018 sylvatic yellow fever outbreak in Brazil

Abstract: Platyrrhini are highly vulnerable to the yellow fever (YF) virus. From 2016 to 2018, the Atlantic Forest of southeast Brazil faced its worst sylvatic YF outbreak in about a century, thought to have killed thousands of primates. It is essential to assess the impact of this epidemic on threatened primate assemblages to design effective conservation strategies. In this study, we assessed the impact of the 2016-2018 YF outbreak on a geographically isolated population of Near Threatened black-fronted titi monkeys (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 65 publications
(142 reference statements)
0
12
0
Order By: Relevance
“…Over 2000 human cases of yellow fever were confirmed related to extensive epizootic transmission in the South, Southeast and Northeast regions of Brazil between 2016 and 2021 24 . Dramatic declines in NPs were observed concurrently during the outbreak, including for critically endangered and vulnerable species 25 . The worst affected region contains three of South America's most populous cities (São Paulo, Rio de Janeiro, and Belo Horizonte) alongside the Atlantic Forest, a heavily deforested and fragmented biome that nevertheless hosts one of the highest diversity of vertebrates worldwide 26,27 .…”
Section: Mainmentioning
confidence: 99%
“…Over 2000 human cases of yellow fever were confirmed related to extensive epizootic transmission in the South, Southeast and Northeast regions of Brazil between 2016 and 2021 24 . Dramatic declines in NPs were observed concurrently during the outbreak, including for critically endangered and vulnerable species 25 . The worst affected region contains three of South America's most populous cities (São Paulo, Rio de Janeiro, and Belo Horizonte) alongside the Atlantic Forest, a heavily deforested and fragmented biome that nevertheless hosts one of the highest diversity of vertebrates worldwide 26,27 .…”
Section: Mainmentioning
confidence: 99%
“…While forest cover and connectivity explain mammal diversity in fragmented landscapes, hunting pressure, and altitude (which is also related to forest productivity) are the main drivers that explain mammal diversity and abundance in large continuous forests of Serra do Mar (Galetti et al 2009b. The outbreak of yellow fever in the last few years is likely to have caused the local extinction of howler monkeys in some forest remnants and population decline in many protected areas (Berthet et al 2021).…”
Section: Where Are the Mammals In São Paulo State?mentioning
confidence: 99%
“…For the nonhuman primates (NHPs), the impact was even greater, the health agencies had at least 2276 confirmed cases of yellow fever (YF) in the two most prominent periods (December 2016/July 2017 and July 2017/June 2018) (Ministério da Saúde, 2017, 2018). Among the most impacted were the endemic populations of the Critically Endangered northern muriqui ( Brachyteles hypoxanthus ; Strier et al, 2019) and golden‐lion tamarins ( Leontopithecus rosalia ; Dietz et al, 2019), and the Near Threatened black‐fronted titi‐monkeys ( Callicebus nigrifrons ; Berthet et al, 2021) as the virus continued to spread to areas beyond the limits where it is considered endemic (Cavalcante & Tauil, 2017; N. C. C. A. Fernandes et al, 2021; Rezende et al, 2018). From 2019 onwards, the YFO had reached the southernmost states of Paraná and Santa Catarina, by late 2020 and early 2021, the virus reached Rio Grande do Sul, causing the deaths of howler monkeys ( A. guariba clamitans ) (Andrade et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…In the Americas, the yellow fever virus (YFV) is a great challenge to conservationists and to health authorities as the disease can quickly develop lethal forms of infections in humans and NHPs. The severity of infections may reflect the different co‐evolutionary processes of the hosts and the virus, which was relatively recently introduced from the African continent, thus the disease lethality still higher than the levels reported in Africa (Klitting et al, 2018; Monath & Vasconcelos, 2015), In contrast, South America primate genera such as Sapajus , Callicebus , Callithrix, Brachyteles , and Alouatta differ in their vulnerability to the YFV (Berthet et al, 2021; Bicca‐Marques & Freitas, 2010; Cunha et al, 2020; Klitting et al, 2018; Mares‐Guia et al, 2020; Moreno et al, 2013, 2015; Sacchetto et al, 2020; Strier et al, 2019). Studies that investigated YFV infection found that there are significant differences in viral loads between the genera Alouatta and Callithrix , with the later showing a lower viral load and not developing fatal form of infections (Mares‐Guia et al, 2020; Sacchetto et al, 2020).…”
Section: Introductionmentioning
confidence: 99%